Use of a Double Reverse Traction Repositor versus a Traction Table for the Treatment of Intertrochanteric Femur Fractures: A Comparative Study. Issue 4 (5th May 2021) - Yan, Mingming; Kuang, Letian; Ni, Jiangdong; Ding, Muliang; Wang, Junjie; Huang, Jun; Song, Deye
Abstract : Objective: The aim of the present study was to compare the clinical results for unstable femoral intertrochanteric fractures treated with a double reverse traction repositor (DRTR) and those treated using a traction table with the Asia proximal femoral nail antirotation (PFNA‐II). Methods: A retrospective study was performed including 95 patients with AO/OTA type 31‐A2 and 31‐A3 unstable femoral intertrochanteric fractures who underwent DRTR or traction table‐facilitated PFNA‐II nailing from April 2015 to December 2018 in our traumatic center. Demographics, duration of operation, blood loss, part loading time after surgery, fracture healing time, and early and late complications were assessed. Clinical and radiological outcomes were collected to compare the differences between the two groups. Results: A total of 95 unstable intertrochanteric fracture patients treated with the PFNA‐II were analyzed. Of these cases, 56 patients were treated with a DRTR and the other 39 patients were treated using a traction table to achieve fracture reduction. No patients died during surgery and hospitalization. There were no significant differences in respect to demographics and fracture characteristics of cases enrolled. The total operative time was significantly longer in the traction table group than in the DRTR group (72.5 ± 6.1 min for the traction table and 63.0 ± 4.1 min for the DRTR group, P < 0.001). No significant differences were observed in intraoperative blood loss and duration of hospitalization. The periods of follow up ranged from 12 to 31 months among all patients. At the last follow up, the Harris hip score (HHS) in the DRTR group was excellent in 10 patients (17.9%), good in 36 (64.3%), fair in 8 (14.3%), and poor in 2 (3.6%). These scores were comparable to those in the traction table group, which were: excellent in 8 patients (20.5%), good in 24 (61.5%), fair in 6 (15.4%), and poor in 1 (2.6%). Regarding the radiological evaluation, excellent rates of reduction rate were achieved in 39 cases (69.6%) in the DRTR group, which was comparable to 19 cases (48.7%) in the traction table group. In addition, the mean fracture healing time after surgery was 20.6 ± 2.3 weeks in the DRTR group and 21.4 ± 3.4 weeks in the traction table group, which did not reach a significant difference ( P = 0.18). During the follow up, 6 cases of thigh pain, 4 cases of deep vein thrombosis, and 1 case of fracture of the anterior superior iliac spine were reported in the DRTR group. In the traction table group, there were 2 cases of deep vein thrombosis and 3 cases of thigh pain. Conclusion: When using the PFNA‐II for unstable intertrochanteric fractures, the DRTR was superior to the traction table in respect to operative time and duration of patient position, despite an additional ipsilateral anterior superior iliac spine (ASIS) incision and drilling of the ASIS and the femur condyle. Abstract : Use of a DRTR or a traction table achieves similarly successful results for unstable intertrochanteric fractures. Moreover, the DRTR is superior to the traction table with respect to operative time and duration of patient position.